2019
DOI: 10.1155/2019/8450158
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Crude Extract and Isolated Constituents of theDichrostachys cinereaBark towards Multifactorial Drug-Resistant Cancer Cells

Abstract: The effectiveness of anticancer chemotherapy is greatly impeded by the resistance of malignant cells to cytotoxic drugs. In this study, the cytotoxicity of the crude extract (DCB) and compounds isolated from the bark of Dichrostachys cinerea, namely, betulinic acid (1), glyceryl-1-hexacosanoate (2), 7-hydroxy-2-(4-hydroxyphenyl)-4H-chromen-4-one (3), and 6-hydroxy-2-(4-hydroxyphenyl)-4H-chromen-4-one (4), was investigated. The study was extended to the assessment of the mode of induction of apoptosis by DCB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…Regarding the structure-activity relationship, it appears that pentacyclic triterpene 1 is different from 2 by the presence of the carboxyl group (-COOH) in C-13 ( Figure 1 ); the presence of this −COOH group significantly enhanced the cytotoxic activity of triterpene 1 , with IC 50 values ranging from 14.44 µ M to 44.20 µ M in cancer cells tested whilst no IC 50 value at up to 100 µ M was recorded with triterpene 2 ( Table 1 ). Betulic acid, another pentacyclic triterpene with–COOH in C-17, previously displayed good cytotoxicity against all cancer cell lines tested in this work [ 41 ], illustrating the importance of the carboxyl function in the cytotoxicity of pentacyclic triterpenes. Concerning xanthones, though 5 was active in all tested cancer cell lines, 3-5 displayed moderate activities ( Table 1 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Regarding the structure-activity relationship, it appears that pentacyclic triterpene 1 is different from 2 by the presence of the carboxyl group (-COOH) in C-13 ( Figure 1 ); the presence of this −COOH group significantly enhanced the cytotoxic activity of triterpene 1 , with IC 50 values ranging from 14.44 µ M to 44.20 µ M in cancer cells tested whilst no IC 50 value at up to 100 µ M was recorded with triterpene 2 ( Table 1 ). Betulic acid, another pentacyclic triterpene with–COOH in C-17, previously displayed good cytotoxicity against all cancer cell lines tested in this work [ 41 ], illustrating the importance of the carboxyl function in the cytotoxicity of pentacyclic triterpenes. Concerning xanthones, though 5 was active in all tested cancer cell lines, 3-5 displayed moderate activities ( Table 1 ).…”
Section: Discussionmentioning
confidence: 71%
“…To the best of our knowledge, the cytotoxicity of the crude extract and compounds 1 , 2 , 3 , 7 , and 8 on the studied cell lines is being reported, herein, for the first time. Betulinic acid ( 6 ) is a well-known cytotoxic compound and has previously been found active towards the cancer cell lines tested in the present work, with IC 50 values ranging from 7.65 µ M (in CEM-ADR5000 cells) to 44.17 µ M (in HepG2 cells) [ 41 ]. Although it was not further tested, herein, compound 6 can be ranked amongst the best active principles of Hypericum roeperianum.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were kept at −20 °C for 24 h. After washing with cold PBS, cells were re-suspended in cold PBS with 20 ug/mL RNAse for 1 h at room temperature and then stained with 50 μg/mL propidium iodide (PI) (Thermo Fisher Scientific, Darmstadt, Germany). Cell cycle analysis was performed using the BD Accuri TM C6 Flow Cytometer (BD Biosciences, Heidelberg, Germany) [ 47 , 48 , 49 , 50 ]. Cell cycle data were analyzed with ModFit LT™.…”
Section: Methodsmentioning
confidence: 99%
“…One million of CCRF/CEM or KMS-12-BM cells were exposed to sencha-MeOH and -H 2 O extracts, a solvent control (DMSO), or a positive control hydrogen peroxide (H 2 O 2 ) in a 6-well plate for 48 h. Then, the measurement of ROS production was evaluated with the cell-permeable and non-fluorescent 2′,7′-dichlorodihydrofuorescein diacetate (H2DCFHDA) (Sigma-Aldrich, Taufkirchen, Germany), which could be converted to the highly fluorescent 2′,7′-dichlorofluorescein (DCF) by intracellular hydroxyl and peroxyl. Cells were measured with BD Accuri TM C6 Flow Cytometer using FL-1 the channel (488 nm excitation) [ 48 , 53 ]. 10 4 events were counted for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…The crude extract and isolated constituents of the Dichrostachys cinerea bark was also reported against multifactorial drugresistant Cancer Cells by Mbaveng et al, (2019). The betulinic acid and 6-hydroxy-2-(4-hydroxyphenyl)-4H-chromen-4oneisolated from D. cinerashowed cytotoxic effects towards the 9 tested cancer cell lines with IC50 below 50 μM (Mbaveng et al,2019). Tatematsu et al (1991) reported two cytotoxic secondary metabolites isolated from Securinega virosa i.e.…”
mentioning
confidence: 95%